Pemanfaatan Agregat Sungai Mawa Kecamatan Cendana Dalam Campuran AC-WC - Irene Sion Kondo Sosang; Alpius; Rais Rachman (Paulus Civil Engineering Journal, 2020)
This research is intended to examine the characteristics of AC-WC mixture by utilizing aggregates from the Mawa river, Cendana District. The method in this research is to conduct a series of characteristics testing in the form of fine aggregates, coarse, and fillers then design the composition of the mixture then manufacture test specimens in the form of AC-WC mixture and Marshall test to obtain the mixture characteristics and Marshall Immersion test to obtain an Immersion Index (IP) / Index Residual Strength (IKS) / Durability of mixes with optimum asphalt content. The results of the study showed that the characteristics of the pavement material in the form of aggregates from the Mawa river, Cendana District meet the specifications as road surface lining materials. Through the Marshall test the AC-WC mixture characteristics obtained with asphalt content of 5%, 5.5%, 6%, 6.5%, 7% meet the requirements issued by the Directorate General of Highways of the Ministry of Public Works of the Republic of Indonesia, General Specifications 2018. Results Marshall Immersion testing of AC-WC mixture at optimum asphalt content of 7% gets an Immersion Index (IP) / Residual Strength Index (IKS) / Durability of a mixture of 94.81% which means it exceeds the boundary requirement of ≥ 90% so the mixture is resistant to immersion in water .